The Impact Of Microfinance Services On Malaysian B40 Households’ Socioeconomic Performance: A Moderated Mediation Analysis - W Muhammad Zainuddin B Wan Abdullah; Sarina Binti Ismail; Hafiz Muhammad Zia-ul-haq; Wan Nur Rahini Aznie Zainudin (International Information and Engineering Technology Association, 2024)
Indexed by Scopus/ERA